Therapeutic Modulation Of Peripheral Blood Cells And Inflammatory Indices During 52 Weeks Of Risankizumab In Responder Patients With Moderate-to-Severe Psoriasis: Results From A Multicenter Prospective Study - Di Cesare, Antonella; Rosi, Elia; Trovato, Emanuele; Pescitelli, Leonardo; Panduri, Salvatore; Manzo Margiotta, Flavia; Michelucci, Alessandra; Capalbo, Eugenio; Dragotto, Martina; Magnano, Michela; Rossari, Susanna; Savarese, Imma; et al. (Dermatology Practical & Conceptual, 2025)
Introduction: Whole blood cells and derived indices can be used as a read-out of the inflammatory pathogenic processes in many human diseases, including psoriasis. Indeed, systemic treatments with special regard to anti-IL-23 agents could exert anti-inflammatory and disease modifying effects; however, there is still a lack of conclusive data. Objectives: We aimed to assess the therapeutic effect of risankizumab on whole blood cells and inflammatory indices in psoriatic patients. Methods: We performed a prospective multicenter observational study on adult patients with moderate-to-severe psoriasis who underwent risankizumab therapy for at least 52 weeks. Blood cell count, CRP, and ESR were prospectively recorded for each patient included in the study, at routine visits up to week 52. The ratio between peripheral cells, namely NLR, PLR, MLR, SII, and PIV, were calculated and compared at time 0 and at weeks 12, 24, and 52 of treatment. At different timepoints, modulation of laboratory values and derived indices and their correlation with disease severity and response to treatment were analyzed. Subanalysis of very early responders and late responders was performed as well. Results: We observed a progressive reduction in inflammatory indices such as CRP, ESR, NLR, and SII during treatment, with prominent modification involving SIRI as well, in patients who had a very early and almost complete response to risankizumab. Reduction in neutrophils and MPV, a transient increase in eosinophils at week 12, and a progressive increase in peripheral basophils were associated with therapeutic response. Conclusion: Risankizumab promotes a progressive anti-inflammatory effect, more prominent in patients with a faster response in the early phases of treatment.